Effects or curcumin and tocotrienol on pro-inflammatory cytokines in experimental acute uveitis / Aliza Hani Mansor - Mansor, Aliza Hani (2013)
Inflammation of the uvea is termed as uveitis. As in any inflammatory diseases, several inflammatory mediators are involved in the pathogenesis of the disease. Past studies has shown that tocotrienol have antioxidant, anticancer, neuroprotective and cholesterol lowering properties. Some studies have shown that tocotrienol is able to block the NF-KP pathway, which subsequently, may also effect the several inflammatory mediators released by the activation of NF-KP. In our study, the rats are first induced by a single footpad injection of lipopolysaccharide (LPS) which has been dissolved in saline. Negative control rats receive footpad injection of saline only. 3 hours after injection, the rats are given empty liposomes, 0.04% or 0.03% liposomal tocotrienol. 24 hours after the induction of uveitis, slit lamp examination were done to assess the degree of inflammation and the eyes were enucleated for gene expression study. The severity of uveitis in the group receiving treatment of 0.04% liposomal tocotrienol was higher as compared to the positive control group. On the other hand, group receiving treatment of 0.03% liposomal tocotrienol, showed much more less severity as compared to both the positive control group and group receiving 0.04% liposomal tocotrienol. In conclusion, tocotrienol is able to reduce the degree of uveitis, but high concentration of tocotrienol could worsen the inflammation due to its pro-inflammatory activity.